Phase Extracting Imaging by Stacking Defocus Transport of Intensity Equation - Suwan Plaipichit; Jakkapol Visessamit; Surawut Wicharn; Prathan Buranasiri (Digital Holography and 3-D Imaging 2022, 2022)
The investigation of cells was performed using TIE. The phase imaging using a stack of low defocus intensity images has shown better results of the cell edge and shape comparing with the traditional one.
Keywords: Digital Holography and Microscopy; Advanced X-ray Imaging Techniques; Optical measurement and interference techniques